An Analytical Study of Avicenna‘s Hierarchical Metaphysical Structure of Soul - Kareem Al-Salahi, Ayad (International Journal of Psychosocial Rehabilitation, 2020)
Avisennaµs was very interested in psychology, therefore, he was one of the pioneers of this field in the ancient and medieval history. It is obvious that he adopted the traditional classification of philosophical sciences which is originated to Aristotle; sciences were classified into practical and theoretical. Soul is one of the topics which are dealt with in the theoretical sciences, ( Al-Musawi, 1982 : 137).That is not surprising because Ibn Sina believes that human beings consist of soul and body, so he was interested in them both; his law was a search of satisfaction concerning body, and his philosophy, concerning logic, nature, and Divine concepts was based on the human soul. In logic, he asserts the existence of priorities, their instinctiveness in mind, and they are the essence of every intellection. In natural matters, he classifies creatures into; inanimate, growing and sensitive souls, and talking souls and their destination, ( Nadir,1959: 232). Ibn Sina is considered the representative of the doctrine that believes in the spiritual resurrection. Thus, Al-Ghazali and some others, who adopt physical resurrection, argue, criticize, and try to defeat this doctrine through defeating Ibn Sina's views.Since Ibn Sina classifies souls into two major types; the first includes the natural matters; plant, animal, human, in addition to different senses, mutual feelings, imagination, and reasonableness. The second type is closer to metaphysics; its search in the field of soul is based on the reality of soul and its destination after death,( Al-Iraqi,1975 : 144).The present study is within the metaphysical scope which is concerned with the concept of the external structure of soul; its definition, existence, and nature. Then, the body- soul relationship is discussed. The study ends with discussing the problem of soul immortality and return, ( Aal Yasseen,1984 : 171), due to significant introductions.